PEMANFAATAN MEDIA CAKRA INDONESIA UNTUK MENINGKATKAN PENGUASAAN KOSA KATA DALAM MATA KULIAH ACADEMIC AND SCIENTIFIC VOCABULARY MAHASISWA PENDIDIKAN BAHASA INGGRIS UNIVERSITAS ISLAM BALITAR BLITAR - Sutanti, Nita (Universitas Islam Balitar, 2020)
Observation in class shows that there was a problem in mastering vocabulary. This research was conducted with the aim of increasing mastery of academic and scientific vocabulary through the use of Cakra Indonesia media. This research is a Classroom Action Research (CAR). The subjects of the study were the fourth semester students of English Education Department. The implementation of CAR is in the even semester of 2018/2019 academic year. In pre-action learning outcomes of students showed an average of 70.42 Increased to 75.41 in the first cycle, and increased to 82.36 in the second cycle. Thus the conclusion reached about the use of Cakra Indonesia media can improve the mastery of academic and scientific vocabulary in academic and scientific vocabulary courses of English Education students at Balitar Islamic University, Blitar. This was proved by the success of students in each cycle increases, even in the second cycle the success rate of students reaches 88.89%.